Dissecting Heat Tolerance in Bread Wheat (Triticum aestivum L.): A Quantitative Trait Analysis via Correlation and Path Coefficients: Quantitative heat tolerance trait analysis in wheat - Binita Dobariya; Ashwin Pansuriya; Deep Vekaria; Chandrakant Singh; Jaysukh Savaliya (Journal of Cereal Research, 2025)
The study was undertaken to estimate genotypic and phenotypic correlation coefficients and path analysis for grain yield per plant and its components by using 48 genotypes of wheat. The grain yield per plant has significant and positive genotypic and phenotypic correlations with biological yield per plant and harvest index under timely sown (D1) condition. Under late sowing (D2)) condition, grain yield per plant had highly significant and positive genotypic and phenotypic correlation with harvest index and biological yield per plant. Chlorophyll content at anthesis was significantly but negatively correlation with grain yield per plant at both levels. The path coefficient analysis revealed that the biological yield per plant, harvest index, days to 50% flowering and grain filling period showed high and positive direct effect on grain yield per plant under timely sowing condition. While, in case of late sowing condition, path coefficient analysis revealed that, biological yield per plant, harvest index and days to 50% flowering exhibited high and positive direct effect on grain yield per plant. Thus, these characters were identified as the most important yield components and due emphasis should be placed on these characters while selecting for high yielding genotypes in wheat.